2014
DOI: 10.1007/s00339-014-8904-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of defects in the tensile properties of silicene

Abstract: Effects of vacancies and Stone-Wales defects on the mechanical properties of silicene are investigated through molecular dynamic finite element method with Tersoff potential. Young's modulus, Poisson's ratio and uniaxial tensile stress-strain curves are considered in the armchair and zigzag directions. It is found that pristine and lowly defective silicene sheets exhibit almost the same elastic nature up to fracture points. However, a single defect weakens significantly the silicene sheet, resulting in a consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…A wrinklon occurs and responds to the local transition area, which is needed to merge two wrinkles of wavelength into a larger one. Similar behavior has been discussed with regard to the wrinklons of graphene sheets [18,21]. The fracture gradually becomes large as the strain increases continuously until a strain of 0.3, as shown in Figure 1d.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…A wrinklon occurs and responds to the local transition area, which is needed to merge two wrinkles of wavelength into a larger one. Similar behavior has been discussed with regard to the wrinklons of graphene sheets [18,21]. The fracture gradually becomes large as the strain increases continuously until a strain of 0.3, as shown in Figure 1d.…”
Section: Resultssupporting
confidence: 78%
“…Table 1 shows the lattice parameters and the geometric structure of the silicene at equilibrium state. For comparison, Table 1 also includes previous studies of MD and density functional theory (DFT) calculations [17,18,19,20]. In this study, the angle between neighboring bonds was taken as θ 0 = 117.98° and the bond length r 0 = 2.32 Å.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…We have used MDFEM to analyze the mechanical properties of various hexagonal sheets, see e.g. [22][23][24]. MDFEM with Stillinger-Weber potential was implemented in our previous work [24] for phosphorene.…”
Section: Framework For Analysismentioning
confidence: 99%
“…Therefore, a deep understanding of defects is highly desirable before fabrication of large-scale high-quality silicene layers for device applications. Recently, several typical point defects, including Stone-Wales (SW) rotation, single and double vacancies (SVs and DVs), and silicon adatoms in freestanding silicene have been systematically investigated using density functional theory (DFT) calculations, focusing on the geometries, energetics, and effects on electronic properties [40][41][42][43][44][45][46][47][48][49][50]. It was found that the SWs and DVs may induce small gaps in silicene, while the SV defect leads to a semimetallic-to-metallic transition in silicene.…”
Section: Introductionmentioning
confidence: 99%